2011
DOI: 10.1007/s10482-011-9608-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Helicobacter pylori cagE genotyping in addition to cagA genotyping: a Bulgarian study

Abstract: Associations of Helicobacter pylori cagE status with complex patient characteristics remain to be elucidated in Eastern Europe. The aim of this study was to assess the frequencies of cagE gene and cagA/cagE combinations in H. pylori strains from symptomatic Bulgarian patients and to improve cagA detection. cagA and cagE genotypes were evaluated in 219 patients with single-strain infections. In total, 84.9% of strains were cagA (+), while 68.5% were cagE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…This rate agrees with results obtained from Brazil, and Bulgaria but was higher than that obtained in Portugal and United States (Oleastro et al, 2003;Podzorski et al, 2003;Garcia et al, 2010;Boyanova et al, 2011). The fact that H. pylori strains exhibit different patterns of adherence to gastric mucosa cells in adults and children can be an explanation of the low prevalence of babA2 in children (Blom et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…This rate agrees with results obtained from Brazil, and Bulgaria but was higher than that obtained in Portugal and United States (Oleastro et al, 2003;Podzorski et al, 2003;Garcia et al, 2010;Boyanova et al, 2011). The fact that H. pylori strains exhibit different patterns of adherence to gastric mucosa cells in adults and children can be an explanation of the low prevalence of babA2 in children (Blom et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…We found that the iceA2 gene (57.1%) was the predominant genotype, supporting the findings of pediatric studies in Brazil (68.9%), Israel (52%), and the Midwestern United States (84%) [25,28,33] . The prevalence of cagE was found in 24.5% of H. pylori isolates in Israel [28] , 59% in Canada [5] , and 41.7% in Bulgaria [26] . The cagE gene was detected in 11 (22.4%) out of 49 isolates, and no significant association was found between the cagE and peptic ulcers in children in this study, consistent with a study by Benenson et al [28] .…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of H. pylori babA2 was 17.2% in Portugal, 36% in the Midwestern United States, 84.4% in Brazil, and 66.7% in Bulgaria [2,25,26,33] . In the present study, the babA2 gene was detected in 40.8% of the H. pylori isolates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The frequent deletion of cagA3 compared to cagA1 and cagA2 in the control strains reported by Matar et al was attributed to decreases pathogenicity (9). Prevalence of cagA positive strains differs between the countries and is the highest in East Asia (90%), Japan (100%) (21) and Bulgaria (84.9%) (22). The moderate prevalence was found in Iran (62%) (23), Slovenia (61%) (24), Columbia (64%) (21), Turkey (49%) (25), Equador (46%) (26) and Portugal (31.8%) (27).…”
Section: Discussionmentioning
confidence: 99%